Natural Course of Fetal Hyaloid Artery: SlowflowHD Longitudinal Study. (3rd December 2021) - Hata, Toshiyuki; Koyanagi, Aya; Yamanishi, Tomomi; Bouno, Saori; Takayoshi, Riko; Miyake, Takahito
Abstract : Objective: To assess the natural course of the fetal hyaloid artery (FHA) using Slow flow HD during pregnancy. Methods: One‐hundred and eighteen normal fetuses were studied longitudinally using Slow flow HD to assess the natural course of FHA at 18–21 + 6, 28–31 + 6, and after 35 weeks of gestation. Blood flow of FHA with/without its branches (BF) was evaluated using Slow flow HD, and the band of FHA without blood flow (Band) was identified in each gestational period. The natural course of FHA was classified into six types: Type A, not detected (ND) in each gestational period; Type B, Band at 18–21 + 6 weeks; Type C, Band at 18–21 + 6 and 28–31 + 6 weeks; Type D, BF at 18–21 + 6 weeks; Type E, BF at 18–21 + 6 weeks and Band at 28–31 + 6 weeks; Type F, BF at 18–21 + 6 and 28–31 + 6 weeks. Results: BF, Band, and ND were 83.5, 15.5, and 1.0% at 18–21 + 6 weeks, 8.8, 15.5, and 75.7% at 28–31 + 6 weeks, and 0, 0, and 100% after 35 weeks, respectively. Type A was 1.0%, Type B was 13.6%, Type C was 1.9%, Type D was 61.2%, Type E was 13.6%, and Type F was 8.7%. Conclusions: The presence of FHA blood flow before 30 weeks of gestation should be regarded as a physiologic phenomenon in normal fetuses.